PENGARUH KEKUATAN IMPAK POLIESTER BERPENGUAT SERAT BAMBU HAUR DAN FIBERGLASS PADA APLIKASI BUMPER MOBIL - Raliannoor Raliannoor; A'yan Sabitah (POLITALA PRESS, 2020)
Abstract. The process of developing composite materials is greatly increasing, the need for quality composite materials and the development of composite manufacturing technology are increasingly dominating in the machinery industry. The aim of this research is to develop a composite material with bamboo fiber reinforcement and glass fiber as an alternative to automotive raw materials to replace plastic. Preparation of composite specimens with each reinforcement with a volume fraction of 2%, 2.5%, and 3%. The polymer material used is Yukalac BQTN 157-EX polyester as the matrix. With haur bamboo fiber and fiberglass as reinforcement. Making specimens using the hand lay up method. The test carried out is the impact test of composite specimens. The Impact Test is carried out using the ASTM D 5896 standard. Based on the test results, it can be concluded that the effect of fiber volume fraction on the characteristics of composite samples for impact test. Composite strengthened with bamboo haur and fiberglass powder at 2.5% weight volume fraction has the most ideal characteristic, which has an average impact strength of 0.8412 J/mm2. , and with an average impact strength of 0.3180 J/mm2 at a weight volume fraction of 2.5%. Equivalent to automotive raw materials, namely to develop polyoxymethylene alternative plastic materials.